Pengaruh Green Marketing dan Brand Image Terhadap Loyalitas Pelanggan pada Starbucks CoffeeLiving World Pekanbaru - Putri Khairani; Mashur Fadli (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to determine and analyze the influence of green marketing and brand image on customer loyalty at Starbucks Coffee Living World Pekanbaru. The background of this study is based on increasing competition in the coffee industry, changes in consumer lifestyles that are increasingly environmentally conscious, and the importance of brand image in building long-term relationships with customers. The method used in this study is descriptive and quantitative. The number of samples in this study was 100 people with the sampling technique using purposive sampling. The data analysis technique used is multiple linear regression analysis. In this study, the results obtained are Green Marketing (X1) has a positive and significant effect on customer loyalty (Y), Brand Image (X2) has a positive and significant effect on customer loyalty (Y), and Green Marketing (X1) and Brand Image (X2) have a positive and significant effect on customer loyalty (Y) at Starbucks Coffee Living World Pekanbaru